Patients' knowledge about medication prescription in the emergency service - Thaynara Paola de Carvalho; Meiry Fernanda Pinto Okuno; Cassia Regina Vancini Campanharo; Maria Carolina Barbosa Teixeira Lopes; Ruth Ester Assayag Batista
ABSTRACT Objective: To identify which orientations were received by the patient about the medication prescription and which professional performed it; to evaluate the patients' knowledge about prescription drugs and to correlate it to socioeconomic variables, comorbidities, and the frequency with which the patient seeks emergency service; and to evaluate the knowledge about the medication prescribed after the health care. Method: This was a cross-sectional study on 304 patients that received emergency service's discharge along with medication prescription. Applied instruments: sociodemographic characterization and evaluation of the knowledge about the prescribed medication. We used a descriptive and inferential analysis. Results: Most subjects had no doubts about how or for how long to take the medication; and presented questions about adverse reactions and what to do in case of forgetting to take the medication doses. There was a significant association between age; educational level; comorbidity; the frequency of emergency service's use; and knowledge about medications. Conclusion: a total of 48% of the patients declared to need information about adverse effects and what to do if they forget to take the medication.